Effect of the faique (Acacia macracantha) on the nutritional value of guinea grass (Panicum maximum Jacq.) in a silvopastoral system - Romero Delgado, Gelver (2020)
The aim of this study was to determine the growth rate and nutritional quality of Guinea grass (Panicum maximum Jacq) under a silvopastoral system with the faique tree (Acacia macracantha). The evaluation included two seasons (rainy and dry) and three treatments: (1) under the canopy of the young tree, (2) under the canopy of the medium-size tree, and (3) outside the canopy of the tree. The trees were classified according to the diameter at chest height. The growth and quality of the grass were measured by the method of cutting and separation and subsequent laboratory analysis. The growth rate ranged from 71.09 to 51.15 kg DM/ha/d, outside and inside the tree canopy, respectively, in the rainy season. Crude protein varied from 10.58, 12.79 and 13.88% (rainy season) and 8.93, 10.26 and 11.99% (dry season) outside the tree canopy, under the young tree canopy and under the middle tree canopy respectively (p<0.05). The calcium content in the grass was statistically (p<0.05) higher under the middle tree canopy (0.23%) than outside the tree canopy (0.20%) in the rainy season. The phosphorus in the grass varied significantly (p<0.05) between 0.72, 0.83 and 0.91% (rainy season) and 0.73, 0.87 and 1.06% (dry season), outside the tree canopy, under the canopy of the young tree and under the canopy of the medium tree, respectively. The study revealed that the presence of leguminous trees (Acacia macracantha) within the paddocks improves the nutritional quality of the Panicum maximum Jacq pasture.